Knowledge and awareness of bovine tuberculosis associated with raw milk and under-cooked meat contamination among cattle farmers in selected parts of zambia. - Anthony Phiri; Emmanuel Likulunga; Adriace Chauwa; Mildred Zulu; Beatrice Kankhuni; Ngula Monde; Sydney Malama (PLoS Neglected Tropical Diseases)
Background Bovine tuberculosis (bTB) is a disease of cattle that is transmitted through direct contact with an infected animal or ingestion of contaminated food. Methods A mixed-methods study was conducted in two districts of Zambia, Lundazi and Monze, from December 2021 to June 2022. A cross-sectional survey with 280 respondents, five focus group discussions, and five key informant interviews were conducted. Descriptive statistics were used to analyze quantitative data using R software, while qualitative data was analyzed using Nvivo and content analysis. Results Social and cultural practices were reported to significantly contribute to bTB transmission with risky behaviors including the consumption of undercooked meat and unpasteurized milk, and inadequate protective measures during cattle slaughtering. Overall, 75.3% of male and 70.3% of female respondents expressed a poor level of awareness of bTB transmission. Among cattle farmers, 85.7% lacked formal education, resulting in low knowledge levels, with 99.5% expressing poor awareness. Additionally, findings revealed that 99.5% of cattle farmers had poor awareness of bTB, human doctors/clinicians, and veterinary/para-veterinarians had 100% excellent knowledge. Abattoir workers had good knowledge at 78.3% and cattle businessmen had a fair knowledge level at 96.4%. Overall, bTB awareness varied across occupations, with human and animal healthcare professionals being the most knowledgeable. Conclusions Our study found low levels of awareness and misperception about bTB among cattle farmers. Awareness varied across professionals with educated individuals being more knowledgeable. The consumption of undercooked meat and raw milk highlighted these knowledge gaps. Therefore, it is crucial to conduct public health campaigns to raise awareness about bTB causes, sources of infection, and control measures.